Diagnosis of Dental Fluorosis Made By Undergraduate Dental Students - Mir, Hassam Anjum; Ashfaq, Sana; Shahid, Saleha (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the ability of students to diagnose and decide the correct treatment of fluorosis. Study Design: Cross-sectional study. Place and Duration of Study: Tertiary care Dental Hospital, Rawalpindi, from May to Jun 2017. Methodology: A self-administered questionnaire containing seven pictures of different severity of fluorosis was used to assess the knowledge of students of third-year and final-year BDS. Results: A total of 88 BDS students were included in the study. As for the question of severity, picture-5 had the correct answer 81 (92%), whereas picture-4 had the least correct answer 6 (6.8%). Picture-5 had the correct answer 77 (87.5%) for the treatment question and picture-4 had the least correct answer 6 (6.8%). Picture-5 only showed a significant difference (p= 0.001) with more correct answers for 3rd-year BDS students. More than 50% of the students correctly identified only three of the seven pictures. Severe cases were most correctly diagnosed and mild cases were least correctly diagnosed. Conclusion: Out of the seven lesions shown to the students, only three were correctly diagnosed by more than 50% of the students. Therefore, more lectures and clinical hours for the study of fluorosis are needed.